Ribotypes of clinical Vibrio cholerae non-O1 non-O139 strains in relation to O-serotypes. - Dalsgaard, A. (Cambridge University Press, 1998)
The emergence of Vibrio cholerae O139 in 1992 and reports of an increasing number of other non-O1 serogroups being associated with diarrhoea, stimulated us to characterize V. cholerae non-O1 non-O139 strains received at the National Institute of Infectious Diseases, Japan for serotyping. Ribotyping with the restriction enzyme BglI of 103 epidemiological unrelated mainly clinical strains representing 10 O-serotypes yielded 67 different typing patterns. Ribotype similarity within each serotype was compared by using the Dice coefficient (Sd) and different levels of homogeneity were observed (serotypes O5, O41 and O17, Sd between 82 and 90%: serotypes O13 and O141 Sd of 72; and O2, O6, O7, O11, O24 Sd of 62-66%). By cluster analysis, the strains were divided into several clusters of low similarity suggesting a high level of genetic diversity. A low degree of similarity between serotypes and ribotypes was found as strains within a specific serotypes often did not cluster but clustered with strains from other serotypes. However, epidemiological unrelated O5 strains showed identical or closely related ribotypes suggesting that these strains have undergone few genetic changes and may correspond to a clonal line. Surprisingly, 10 of 16 O141 strains studied contained a cholera toxin (CT) gene, including 7 strains recovered from stool and water samples in the United States. This is to our knowledge the first report of CT-positive clinical O141 strains. The closely related ribotypes shown by eight CT-positive strains is disturbing and suggest that these strains may be of a clonal origin and have the potential to cause cholera-like disease. Despite the low degree of correlation found between ribotypes and serotypes, both methods appears to be valuable techniques in studying the epidemiology of emerging serotypes of V. cholerae.